The Influence of Temperature Variations on Rigid Pavement Concrete Slabs - Mahfuda, Anno; Siswosukarto, Suprapto; Suhendro, Bambang (Journal of the Civil Engineering Forum, 2023)
This research aims to assess the effect of temperature gradient developed within the concrete slab of rigid pavement, and to investigate its impact when incorporated with the traffic load, and the heat transfer pattern. The rigid pavement model considers an isotropic, uniform, and linear-elastic schemes to simulate the material properties. A numerical analysis approach was employed using Abaqus software incorporated with the 3D Solid model. The traffic loads were obtained from the field surveys, while the temperature of the slabs was measured directly on the site. The dimension of the rigid panel is 2.75 m in width, 5 m long, slab thickness of 25 cm, and concrete specification of 41.33 MPa. The results showed that the temperature gradient produced a significant impact on stress development within the concrete slab of rigid pavement. It was observed that the temperature gradient during the daytime generated higher stress than at night, with a value reaching the MOR (Modulus of Rupture). The exposure of the rigid pavement to 500C tends to produce a principle slab stress of 2.395 MPa, while 1.31 MPa was developed due to the traffic load. When the two factors were combined, the concrete slab acquired a maximum principle stress of 3.322 MPa, which is close to the MOR of 83.34% fa. These results showed that the pavement is capable of withstanding stress from temperature gradient and traffic load as indicated by the ratio of less than one (1). However, this ratio is high for fatigue failure mitigation purposes, and this reduces the quality of life of the rigid pavement.